A atividade em um blog feminino: um olhar históricocultural para o trabalho, as trocas e relações dos sujeitos nas redes sociais - Romagnani, Patrícia (2018)
This case study of a female blog from Curitiba, with the contribution of sociohistorical psychology and the theory of activity in line with the Soviets, coupled with González Rey‘s qualitative epistemology, wanted to investigate the exchanges and relations established by subjects in dealing with information and communication technologies while active on blogs and social networks. From the perspective of organizational studies, with a look at subjectivity, this paper has analyzed the processes by which the actors belonging to the organization construct their various forms of rationality. A variety of research instruments have been used, such as individual and collective interviews, complementing sentences, drawing, selfconfrontation and instruction to counterparts. Assessment of the activity structure of Organização Tau, founded in 2008 and growing professionally with great strides, has shown that its purpose is to generate financial gain with productive work, in addition to being a digital influence, and recognizing and building a community with related interests. Tau produces quality content (text, voice, image), improves of readers‘ self-esteem and attracts advertisers. The conclusion is that, although technology potentially integrates criticism of the world and the singularity of subjects, it conforms to the economic logic, particularly to its symbolic and ideological production. Blogging can generate both economic value and symbolic value. This immaterial value sometimes relativizes reality by emphasizing selfesteem, self-acceptance, and consumption. Cult of the image becomes symbolic content, and its subjective activity becomes input for the immaterial work. The subject‘s activity becomes the substance of his/her personality and alienated activity. The thesis maintained here is that a new type of alienation is coming to existence and it is even more perverse, which is the liberation of the body from all sorts of displeasure, obscuring the contradictions present in reality. Technology becomes a form of objective control over subjectivities so distant from rational thought that it hinders critical consciousness building, given that technology is involved in the symbolic creation of capital itself on behalf of the construction of the contemporary subject.